6-(3,5-Dimethyl-1H-pyrazol-1-yl)-2,2′-bipyridine as ligand for Actinide(III)/Lanthanide(III) separation - Girnt, Denise; Roesky, Peter; Geist, Andreas; Ruff, Christian; Panak, Petra; Denecke, Melissa Anne (Inorganic chemistry, 2010)
With the aim of better understanding the selectivity of the established system 2,6-ditriazinylpyridine (BTP) for actinide(III)/lanthanide(III) separations, a related model system was synthesized and studied. The N donor complexing ligand 6-(3,5-dimethyl-1H-pyrazol-1-yl)-2,2′-bipyridine (dmpbipy) was synthesized having a fused N heterocycle ring structure modified from the BTP partitioning ligand, and its extraction performance and selectivity for trivalent actinide cations over lanthanides was evaluated. X-ray diffraction (XRD), extended X-ray absorption fine structure (EXAFS), and time-resolved laser fluorescence spectroscopy (TRLFS) results show that 1:1 complexes are formed, unlike the 1:3 complex for BTP systems. The equilibrium constant for curium complex formation with dmpbipy was determined to be log K = 2.80, similar to that for nitrate. The Gibbs free energy, ΔG(20 °C), of 1:1 Cm-dmpbipy formation in n-octan-1-ol was measured to be −15.5 kJ/mol. The dmpbipy ligand in 1-octanol does not extract Am(III) Eu(III) from HNO3 but was found to extract Am(III) with limited selectivity over Eu(III) (SFAm(III)/Eu(III) ≈ 8) dissolved in 2-bromohexanoic acid and kerosene at pH > 2.4.
Gesehen am 28.03.2023